Burkholderia cenocepacia ET12 transmission in adults with cystic fibrosis. Issue 1 (15th November 2019) - Blanchard, Ana C; Tang, Lin; Tadros, Manal; Muller, Matthew; Spilker, Theodore; Waters, Valerie J; LiPuma, John J; Tullis, Elizabeth
Abstract : This report describes transmission of a Burkholderia cenocepacia ET12 strain (ET12-Bc) at the Toronto Adult Cystic Fibrosis (CF) Centre occurring from 2008 to 2017. Epidemiological and genomic data from 11 patients with CF were evaluated. Isolates were analysed using whole genome sequencing (WGS). Epidemiological investigation and WGS analysis suggested nosocomial transmission, despite enhanced infection control precautions. This was associated with subsequent deaths in 10 patients. ET12-Bc positive patients are no longer cared for on the same unit as ET12-Bc negative patients.